DETERMINAÇÃO DO FATOR DE ATRITO EM DIFERENTES REGIÕES DO DIAGRAMA DE MOODY - Saad, João Carlos Cury; Guzmán Rojo, Daniela Patricia; Gaia, Camila Duane Correa (IRRIGA, 2024)
FRICTION FACTOR DETERMINATION IN DIFFERENT REGIONS OF THE MOODY CHART DANIELA PATRICIA GUZMÁN ROJO1; CAMILA DUANE CORREA GAIA2 E JOÃO CARLOS CURY SAAD3 1Departamento de Engenharia Rural e Socioeconomia, Faculdade de Ciências Agronômicas, Universidade Estadual Paulista (UNESP), Avenida Universitária, nº3780 –CEP 18610-034, Altos do Paraíso, Botucatu, SP, Brasil, E-mail: daniela.guzman.rojo@gmail.com; ORCID ( https://orcid.org/0000-0002-8595-5089 ). 2Departamento de Engenharia Rural e Socioeconomia, Faculdade de Ciências Agronômicas, Universidade Estadual Paulista (UNESP), Avenida Universitária, nº3780 –CEP 18610-034, Altos do Paraíso, Botucatu, SP, Brasil, E-mail:camilagaia7@gmail.com; ORCID ( https://orcid.org/0000-0002-3669-7984 ). 3Departamento de Engenharia Rural e Socioeconomia, Faculdade de Ciências Agronômicas, Universidade Estadual Paulista (UNESP), Avenida Universitária, nº3780 –CEP 18610-034, Altos do Paraíso, Botucatu, SP, Brasil, E-mail:joao.saad@unesp.br, ORCID ( https://orcid.org/0000-0002-8314-7758 ). 1 ABSTRACT Calculating pressure loss (hf) in pipes is essential for sizing pressurized irrigation systems. The Darcy-Weisbach equation is the most recommended method for estimating hf, and it requires the calculation of the friction factor, f. The hypothesis of this research is that general equations for calculating f, which cover the entire Moody diagram, do not always produce results sufficiently close to those obtained from the specific equations for each flow regime. The objective of this study was to evaluate the performance of general f estimation equations across different regions of the Moody diagram (i.e., different flow regimes) and, based on the results, to develop a MATLAB code for its calculation. The results confirmed the hypothesis that general equations for calculating f do not always yield results sufficiently close to those derived from the specific equations for each flow regime. The mean relative error (MRE) was used to measure the accuracy of the equations. Based on the smallest MRE, the following equations were selected for calculating f according to the flow regime: Swamee for the laminar regime, Konakov for the turbulent/smooth regime, Vatankhah for the turbulent/rough and transitional regimes, and the Offor & Alabi equation for the transient turbulent regime. A MATLAB code was developed using these equations to facilitate personal use or integration into software. Keywords: irrigation systems; head loss; hydraulic. GUSMÁN ROJO, D. P.; GAIA, C. D. C.; SAAD, J. C. C. DETERMINAÇÃO DO FATOR DE ATRITO EM DIFERENTES REGIÕES DO DIAGRAMA DE MOODY 2 RESUMO O cálculo da perda de carga (hf) em tubulações é fundamental para o dimensionamento de sistemas de irrigação pressurizados. A equação de Darcy-Weisbach é a mais recomendada para estimar hf e requer o cálculo do fator de atrito, f. A hipótese desta pesquisa é que as equações gerais para cálculo de f, que abrangem todo o Diagrama de Moody, nem sempre produzem resultados suficientemente próximos daqueles obtidos utilizando as equações específicas para cada regime de fluxo. O objetivo deste trabalho foi avaliar o desempenho de equações gerais de estimativa de f nas diferentes regiões do diagrama Moody (regimes de fluxo) e, com base nos resultados, desenvolver um código MATLAB para seu cálculo. Os resultados obtidos confirmaram a hipótese de que as equações gerais de cálculo de f nem sempre produzem resultados suficientemente próximos aos obtidos através das equações específicas quando aplicadas a cada regime de escoamento, tendo utilizado o erro relativo médio (MRE) para medir o ajuste. Com base nos menores MRE, as seguintes equações foram selecionadas para calcular f conforme o regime de fluxo: Swamee para o regime laminar, Konakov para o regime turbulento/suave, Vatankhah para o regime turbulento/áspero e o regime de transição, e a equação de Offor & Alabi para o regime turbulento transitório. Um código MATLAB foi desenvolvido usando essas equações para facilitar o uso pessoal ou para ser incorporado em software. Palavras-chave: perda de carga; fator de atrito; irrigação.